TRANSFORMING PARLIAMENTARY OVERSIGHT: EMERGING TRENDS IN PARLIAMENTARY OVERSIGHT AND DIGITAL GOVERNANCE - Safayev Javohir Omanbayevich (Scholar Express Journals, 2026)
This article examines the prospects for improving parliamentary oversight exercised by the lower chamber, with a particular focus on institutional, legal, and technological dimensions. Special attention is given to the growing role of digital technologies and artificial intelligence in enhancing oversight capacities and facilitating public participation.
Keywords: Parliamentary oversight; lower chamber; legislative control